Pengaruh Penyuluhan Kanker Serviks terhadap Motivasi Keikutsertaan Wanita Melakukan Pemeriksaan Inspeksi Visual Asam Asetat (IVA) - Sawitri, Sawitri; Sunarsih, Sunarsih (Politeknik Kesehatan Tanjungkarang, 2018)
The Data obtained at Panca Jaya of Mesuji Regency on January-June of 2016, out of 430 women of childbearing age who did pap smear and IVA, as many 2 people (0,46%) was detected of having cervical cancer stage 1b, 57 people (13,4%) experiencing pre-cervical cancer lesions which were marked by inflammation, vaginal discharge, redness in the cervix, there was a lump in the cervix and the rest with the normal condition. This study was to be known the influence of cervix cancer socialization toward the motivation of women’s participation in doing Visual Inspection with Acetic Acid (IVA). This research was quantitative research, with Quasi-Experiment research. The population in this research was the women who were at working area of Adi Luhur Community Health Centre, Pancajaya sub-District of Mesuji Regency, on January of 2017 as many 2361 people. Total samples were 96 respondents. Sample taking was proportional random sampling method. Data were collected using questionnaire. The research was done on the date of Mei 1st-20th July 2017. The data was analyzed by univariate (mean) and bivariate (t-test). The result showed that the average score of motivation before the socialization was 42,79 with deviation standard of 7,367. The average score of motivation after the socialization was 62,00 with deviation standard of 6,059. There was the influence of socialization about cervix cancer with the motivation of participating on examination of IVA on women to do Visual Inspection with Acetic Acid (IVA) (t-test> t-table 21,125>1.714, p-value<0,05). It was suggested that Community Health Centre to improve the skill for the staff in the field about socialization technique, also give the facility for sufficient socialization so that they can improve the motivation for the women.